Short- and long-term outcomes of very low birth weight infants in Korea: Korean Neonatal Network update in 2019 - Jang Hoon Lee; YoungAh Youn; Yun Sil Chang (The Korean Pediatric Society, 2020)
Korea currently has the world's lowest birth rate but a rapidly inreasing number of preterm infants. The Korean Neonatal Network (KNN), launched by the Korean Society of Neonatology under the support of Korea Centers for Disease Control, has collected population-based data for very low birth weight infants (VLBWIs) born in Korea since 2013. In terms of the short-term outcomes of VLBWIs born from 2013 to 2016 registered in the KNN, the survival rate of all VLBWIs was 86%. Respiratory distress syndrome and bronchopulmonary dysplasia were observed in 78% and 30% of all VLBWIs, respectively. Necrotizing enterocolitis occurred in 7%, while 8% of the VLBWIs needed therapy for retinopathy of prematurity in the neonatal intensive care unit (NICU). Sepsis occurred in 21% during their NICU stay. Intraventricular hemorrhage (grade ≥III) was diagnosed in 10%. In terms of the long-term outcomes for VLBWIs born from 2013 to 2014 registered in the KNN, the post-discharge mortality rate was approximately 1.2%-1.5%, mainly owing to their underlying illness. Nearly half of the VLBWIs were readmitted to the hospital at least once in their first 1-2 years of life, mostly as a result of respiratory diseases. The overall prevalence of cerebral palsy was 6.2%-6.6% in Korea. Bilateral blindness was reported in 0.2%-0.3% of VLBWIs, while bilateral hearing loss was found in 0.8%-1.9%. Since its establishment, the KNN has published annual reports and papers that facilitate the improvement of VLBWI outcome and the formulation of essential healthcare policies in Korea.